Automatic service abstraction through data, information and knowledge prioritisation. (28th November 2019) - Duan, Yucong; Shao, Lixu; Zhu, Donghai; Yang, Xiaoxian; Sun, Xiaobing
Web service is a popular solution to integrate components when building a software system, or to allow communication between a system and third-party users, providing a flexible and reusable mechanism to access its functionalities. Scientists have been proposing numerous models for defining anything 'as a service (aaS)', including discussions of products, processes, data and information management, and security as a service. Various web service-based systems are prevailing in health service, personalised recommendation provision. We propose a framework towards constructing and searching typed resources in terms of data, information and knowledge through a hierarchy composing data graph, information graph and knowledge graph in order to improve performance in accessing and processing resources. We use cases to illustrate the mechanism of the framework.